DENSITY AND MORPHOMETRIC CHARACTERISTICS OF ANADARA ANTIQUATA IN THE SEAGRASS BED OF BADAK BADAK ISLAND, BONTANG CITY - Siti Aminah Wuru; Aditya Irawan; Lily Inderia Sari (Jurnal Perikanan Unram, 2024)
Anadara antiquata is a zoobenthic associated with seagrass beds and plays an important ecological role in coastal ecosystems, as a source of animal protein and economic value. This study aims to determine the density and morphometric characteristics of A. antiquata in the seagrass beds of Badak Badak Island, Bontang City. The research was carried out in September 2023 – March 2024. The research station is divided into 3 stations, each station is divided into 3 zones, namely the highest tide zone, the highest tide, the lowest tide and the lowest tide. Seagrass and mega A. antiquatasamples were collected using 50x50 cm quadrant transects. Data analysis includes seagrass density as well as density and morphometrics of A. antiquata as well as correlation analysis between seagrass variables and A. antiquata.Seagrass beds are composed of Enhalus acoroides and Cymodocea rotundata with an average density of A. antiquata reaching 27 individuals/m2 and the density of A. antiquata is positively correlated with the density of seagrass stands. Characteristics of shell height and width in a ratio of 1:1.63 .